A 16-year Record of Summer Birds on Truelove Lowland, Devon Island, Northwest Territories, Canada - Pattie, Donald L. (ARCTIC, 1990)
An annual census of adult birds was conducted on the 43 sq km Truelove Lowland, Devon Island, N.W.T., Canada, in the summers of 1970-73 and 1978-89. Forty-three species were seen during 16 years. Of these, 18 species bred regularly on or immediately adjacent to the lowland and 10 were occasional breeders. In addition 15 species were visitors. The highest annual number for most breeding species was two to three times that of their lowest numbers, but some regular breeding species had far greater extremes. Extensions of the breeding range of Pacific Loon (Gavia pacifica), Purple Sandpiper (Calidris maritima), Wheatear (Oenanthe oenanthe), and Water Pipit (Anthus spinoletta) to Devon Island are reported. It is suspected that Hoary Redpolls (Carduelis hornemanni) and Red Knots (Calidris canutus) also nested there once each. A coefficient of detectability is presented for the 16 most frequently seen species. Synchronous fluctuations in Snow Bunting (Plectrophenax nivalis) and Lapland Longspur (Calcarius lapponicus) populations were observed. A possible replacement of Black-bellied Plovers (Pluvialis squatarola) by Lesser Golden-Plovers (P. dominica) was detected. An abrupt disappearance of all colonies of breeding Arctic Terns (Sterna paradisaea) from the lowland was seen in 1989.